2003
DOI: 10.1117/12.497587
|View full text |Cite
|
Sign up to set email alerts
|

Joining of dissimilar materials

Abstract: The combination ofdissimilar materials is a challenging goal for the development ofparts with locally optimised properties. The main goal of these developments are weight reduction, optimisation of properties or the tailoring of the properties for specific applications in combination with an efficient joining technology. However, using conventional high temperature joining technologies, the formation of intermetallic phases within the joining zone is a nearly unavoidable phenomenon when joining dissimilar mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 2 publications
0
13
0
Order By: Relevance
“…However, they still are finer relative to those of base material. That is because some of the broken particles may also grow at the expense of [14,26]. With respect to the HAZ, there is no significant change in the precipitates size compared to base material.…”
Section: Microstructural Evolutionsmentioning
confidence: 85%
See 2 more Smart Citations
“…However, they still are finer relative to those of base material. That is because some of the broken particles may also grow at the expense of [14,26]. With respect to the HAZ, there is no significant change in the precipitates size compared to base material.…”
Section: Microstructural Evolutionsmentioning
confidence: 85%
“…As the dissolution temperature of η is within 300-350°C [13], this phase can be therefore completely dissolved in the stirred zone [14], while it partially dissolves in the TMAZ. On the other hand, due to the short exposure time to high temperatures, it is possible that there is insufficient time for the complete dissolution of this phase.…”
Section: Microstructural Evolutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to reduce the deleterious effect of the intermetallic compounds, their layer thickness needs to be minimized through optimizing processing parameters. It has been demonstrated that minimized intermetallic compound layer thickness of less than 10 mm would result in good mechanical properties [19]. In the present work, although the nugget of FSW of the Al alloy and steel contains Al-Fe intermetallic compounds, they are small with respect to the volume of Al alloy and steel and well distributed, and their size is rather small.…”
Section: Few Intercalated Microstructures and Vortices Can Bementioning
confidence: 95%
“…It is proposed that in FSW, the weld strength of aluminum and steel depends on the IMC, which is often formed during the welding operation of dissimilar materials [ 25 , 46 ]. In addition, process parameters directly affect the thickness of IMC [ 4 , 26 , 28 , 29 , 39 , 40 , 47 , 48 , 49 ]. Hussein et al [ 4 ] presented a cause-effect diagram for IMC thickness formation.…”
Section: Introductionmentioning
confidence: 99%